STUDI KASUS ASUHAN KEPERAWATAN PASIEN TUBERKULOSIS DENGAN MASALAH POLA NAFAS TIDAK EFEKTIF DIBERIKAN TINDAKAN POSISI ORTHOPNEA - Depiyanti, Ni Luh Gede; Sukmandari, Ni Made Ari; Prihandini, Claudia Wuri (Forind Press, 2025)
Tuberculosis is a contagious infectious disease caused by the infectious agent Mycobacterium tuberculosis bacteria which generally attacks the lung organs in humans. The above problems give rise to nursing problems in patients with pulmonary tuberculosis, usually more on the problem of the respiratory system which causes the patient's breathing pattern to be ineffective. One of the non-pharmacological therapies that is effective in reducing shortness of breath in patients with pulmonary tuberculosis is orthopnea positioning. The purpose of this scientific work is to determine the description of nursing care for tuberculosis patients with nursing problems of ineffective breathing patterns given orthopnea positioning measures at UPTD Puskesmas Mengwi I. Descriptive method with a case study approach to the nursing care process carried out in managing clients with ineffective breathing patterns including assessment, nursing diagnosis, intervention, implementation and evaluation. Patient retrieval was carried out using purposive sampling technique in UPTD Puskesmas Mengwi I. The final scientific work of nurses involved as many as three managed patients who were given the action of orthopnea position for 30 minutes. The evaluation of the action was that the patient initially said he had a cough and shortness of breath and increased during activity with an average saturation of 96% and after being given the orthopnea position the nursing problem of ineffectiveness of breathing patterns had been resolved as evidenced by the patient saying he breathed more freely, feeling less tightness with an average oxygen saturation of 98%. Giving orthopnea position can overcome ineffective breathing patterns in Tuberculosis patients So it is recommended that Tuberculosis be given an orthopnea position to overcome overcome ineffective breathing.